2014
DOI: 10.1097/inf.0000000000000219
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Syncytial Virus Disease in Preterm Infants in the US Born at 32–35 Weeks Gestation Not Receiving Immunoprophylaxis

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
102
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 72 publications
(110 citation statements)
references
References 34 publications
6
102
0
2
Order By: Relevance
“…RSVH rates for preterm infants over the last two decades vary in the literature [4, 5, 812, 29, 31, 37, 47, 49, 5157], ranging from ~5/1000 children [4] to >100/1000 children [52, 53], with the highest RSVH rates reported in the lowest gestational age infants (Table 1). In the majority of these studies, RSV immunoprophylaxis was not given.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…RSVH rates for preterm infants over the last two decades vary in the literature [4, 5, 812, 29, 31, 37, 47, 49, 5157], ranging from ~5/1000 children [4] to >100/1000 children [52, 53], with the highest RSVH rates reported in the lowest gestational age infants (Table 1). In the majority of these studies, RSV immunoprophylaxis was not given.…”
Section: Resultsmentioning
confidence: 99%
“…In the PICNIC study [9], the RSVH rate for infants born at 33–35 wGA was 36/1000 children, although center and seasonal variation in hospitalization rates for RSV infection were observed. A more recent study of 32–35 wGA infants followed prospectively from September to May 2009–2010 or 2010–2011 in the US [57], found that the observed hospitalization rate (49/1000 infant-seasons) was similar to that reported in other studies conducted outside the US that employed active surveillance for laboratory-confirmed RSV [9, 44]. In the PONI study [12], a multinational study (23 countries) of 33–35 wGA infants ≤6 months of age during the October 2013 to April 2014 RSV season, the RSVH rate was 61/1000 infant-years.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, a recent study that reviewed the current risk of RSV-related hospitalization in preterm infants at 188 US outpatients' clinics documented that RSV hospitalizations were highest in infants 32-35 weeks gestational age who were 6 months of age or less during November through March with day care attendance or nonmultiple-birth, preschool-aged siblings (8.9 and 9.3 per 100 infant-seasons, respectively). 18 Given these concerns, we suggest that a more transparent re-evaluation of the new COID/Bronchiolitis Subcommittee recommendations should be considered that include:…”
mentioning
confidence: 98%